Synonymy and homonymy in two butterfly species recently described from Colombia (Lepidoptera: Nymphalidae, Satyrinae). / Sinonimia y homonimia en dos especies de mariposas recientemente descritas de Colombia (Lepidoptera: Nymphalidae, Satyrinae) - Ríos-Málaver, Indiana Cristóbal (Anartia, 2020)
ABSTRACT The names Euptychia caerulea Butler, 1869 and Caeruleuptychia sinchi Henao-Bañol, 2019 are recognized as representing the same taxon. Both names should also be considered junior synonyms of Caeruleuptychia urania (Butler, 1867), a sexually dimorphic species of Amazonian distribution. On the other hand, Euptychia similis Henao-Bañol, 2019, so far known from the Colombian Amazon, is a junior homonym of Euptychia similis Butler, 1867. Both entities represent valid, recognizable and distinct species. However, the most recent name is nomenclaturally invalid. Therefore, it is herein proposed its replacement by Euptychia efraini, nom. nov. RESUMEN Los nombres Euptychia caerulea Butler, 1869 y Caeruleuptychia sinchi Henao-Bañol, 2019 se reconocen como representantes de un mismo taxón. Ambos nombres deberían considerarse sinónimos posteriores de Caeruleuptychia urania (Butler, 1867), una especie sexualmente dimórfica de distribución amazónica. Por otra parte, Euptychia similis Henao-Bañol, 2019, hasta ahora conocida del Amazonas colombiano, es un homónimo posterior de Euptychia similis Butler, 1867. Ambas entidades representan especies válidas, reconocibles y distintas. Sin embargo, el nombre más reciente es nomenclaturalmente inválido, por lo cual se propone aquí su reemplazo por Euptychia efraini, nom. nov.